Patient satisfaction with in-centre haemodialysis care: an international survey. Issue 5 (19th May 2014) - Palmer, Suetonia C; de Berardis, Giorgia; Craig, Jonathan C; Tong, Allison; Tonelli, Marcello; Pellegrini, Fabio; Ruospo, Marinella; Hegbrant, Jörgen; Wollheim, Charlotta; Celia, Eduardo; Gelfman, Ruben; Ferrari, Juan Nin; et al.
Abstract : Objectives: To evaluate patient experiences of specific aspects of haemodialysis care across several countries. Design: Cross-sectional survey using the Choices for Healthy Outcomes in Caring for End-Stage Renal Disease (CHOICE) questionnaire. Setting: Haemodialysis clinics within a single provider in Europe and South America. Participants: 2748 adults treated in haemodialysis. Primary and secondary outcomes: The primary outcome was patient satisfaction with overall care. Secondary outcomes included patient experiences of individual aspects of dialysis care. Results: 2145 (78.1%) adults responded to the questionnaire. Fewer than half (46.5% (95% CI 44.5% to 48.6%)) rated their overall care as excellent. Global perceptions of care were uninfluenced by most respondent characteristics except age and depressive symptoms; older respondents were less critical of their care (adjusted OR for excellent rating 1.44 (1.01 to 2.04)) and those with depressive symptoms were less satisfied (0.56 (0.44 to 0.71)). Aspects of care that respondents most frequently ranked as excellent were staff attention to dialysis vascular access (54% (52% to 56%)); caring of nurses (53% (51% to 55%)); staff responsiveness to pain or discomfort (51% (49% to 53%)); caring, helpfulness and sensitivity of dialysis staff (50% (48% to 52%)); and ease of reaching dialysis staff by telephone (48% (46% to 50%)). The aspects of care least frequently ranked as excellent were information provided when choosing a dialysis modality (23% (21% to 25%)), ease of seeing a social worker (28% (24% to 32%)), information provided about dialysis (34% (32% to 36%)), accuracy of information from nephrologist (eg, about prognosis or likelihood of a kidney transplant; 37% (35% to 39%)) and accuracy of nephrologists' instructions (39% (36% to 41%)). Conclusions: Haemodialysis patients are least satisfied with the complex aspects of care. Patients' expectations for accurate information, prognosis, the likelihood of kidney transplantation and their options when choosing dialysis treatment need to be considered when planning healthcare research and practices.